Perilaku Celebrity Worship pada Remaja Perempuan - Juliana Marlin Y Benu; Theodora Takalapeta; Yustina Nabit (Journal of Health and Behavioral Science, 2019)
Celebrity worship behavior is one of the typical behaviors in adolescence. Self-identity issue in the teenage period would look for an ideal figure as a new role model beside their parents. On the other side, teenager’s celebrity worship behavior often raises concerns from parents and other social environments. This study aims to explain the celebrity worship behavior of teenage women. This study is a qualitative study, with interviews as the main data collection tool. The subjects in this study were 3 teenage girls aged 14 to 19 years. The results of the study showed that there are negative and positive effects of celebrity worship behavior for teenagers' lives. Entertainment-social and intense-personal form celebrity worship behavior can see in the entire subject.